Rękopisy literackie Biblioteki Poznańskiego Towarzystwa Przyjaciół Nauk - Hojdis, Bogdan (Slavia Occidentalis, 2017)
This article is a presentation of literary manuscripts stored in the Library of the Poznan Society for the Advancement of Arts and Sciences. The history of taking over the Sulkowski Archives is briefly described together with manuscripts donated by Wawrzyniec Benzelstjerna Engeström and collections donated by Józef Ignacy Kraszewski. The dramas from Wojciech Simon’s Theatrical Library and autographs of famous people including Cyprian Godebski, Ignacy Krasicki, Ludwik Kropiński, Fryderyk Skarbek, Ignacy Tański, Klementyna Tańska Hoffman, Antoni Edward Odyniec, Stefan Garczyński, Juliusz Słowacki, Władysław Bentkoweski, Jan Zachariasiewicz and Tadeusz Różewicz are regarded by experts as very interesting manuscripts owned by the Society, preserved and regained after 1945. The article presents volume II of the „Inventory of manuscripts“ published in 2017 and a project of digitalizing literary manuscripts from the Society’s collection.